تأثير تصميم ريشة توربين ريحي صغير في استخلاص طاقة الرياح - فريد أبو حامد (Tishreen University, 2019)
يعد تصميم ريشة التوربين العنصر الأهم في تحديد الأداء الأمثل للمولد الريحي، وقد بينت الدراسات أن معظم الطاقة المستخلصة من التوربين التي تبلغ 75% تقع عند النصف القريب من طرف الريشة، لذا يجب الاهتمام كثيراً في اختيار السطوح الانسيابية لهذا الجزء من الريشة ]2[، وأن يراعى في التصميم توظيف العناصر القريبة من الطرف لتوليد الطاقة، والجزء القريب من محور الدوران لغرض زيادة عزم الإقلاع ]6[. وقد بين البحث في أثناء إجراء عملية تعديل شكل الريشة لغرض تسهيل عملية التصنيع، إن التغيير البسيط في توزيع طول وتر عناصر الريشة يؤدي إلى انخفاض قليل في معامل الأداء، ولكن أي تغيير في توزيع زاوية ميل عناصر الريشة سيؤدي إلى انخفاض شديد في قيم معامل الأداء، ومن ذلك يتضح أهمية دقة التصنيع في تحسين كفاءة التوربين وتحديد الأداء الأمثل. Blade design is the most important element in specifying the optimal performance of the wind turbine. Studies have shown that most of the energy from the turbine, which is 75% lies at the half part close to the blade edge. Therefore, more attention must be paid when selecting  the flow surfaces  of  this part of blade [2]. When designing, care must be taken that elements close to the edge and the part close to rotation axis should be utilized for the purpose of power generation  and the increase of starting torque respectively [6]. The study has shown that when amending the shape of the blade for the purpose of facilitating the process of manufacturing a simple change in length  distribution of the  blade chord leads to a slight decrease in the coefficient of performance, but any change in the inclination of blade components will result in sharp decrease in the value of  the coefficient of performance. This clarifies the importance of accurate manufacturing to improve the turbine efficiency and specify the optimal performance.